Do poor children become poor adults? Lessons from a cross country comparison of generational earnings mobility - Miles Corak (Institute for the Study of Labor (IZA), 2006)
A cross country comparison of generational earnings mobility is offered, and the reasons for the degree to which the long run labour market success of children is related to that of their parents is examined. The rich countries differ significantly in the extent to which parental economic status is related to the labour market success of children in adulthood. The strength of these associations should not be interpreted as offering a target or menu for the conduct of policy. A framework for understanding the underlying causal process as well as the conception of equality of opportunity is reviewed as a guide for public policy.
Keywords: D31; I13; J62; 330; poverty; generational mobility; Kinder; Armut; Einkommen; Soziale Mobilität; Westeuropa; USA